2016
DOI: 10.1186/s13006-016-0068-7
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of exclusive breastfeeding among HIV-positive mothers: an exploratory qualitative study

Abstract: BackgroundExclusive breastfeeding has the potential to reduce infant and under-five mortality, but research shows the practice is not widespread in resource-poor settings of sub-Saharan Africa. We explored factors influencing the decision to exclusively breastfeed among HIV-positive mothers accessing interventions for prevention of mother-to-child transmission of HIV in selected sites of Zambia.MethodsThis exploratory qualitative study was embedded in research conducted on: HIV and infant feeding; choices and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 36 publications
2
24
1
2
Order By: Relevance
“…This could be a reflection of the misconception that only women with HIV need to practice exclusive breastfeeding, to prevent HIV transmission, and is optional for women without HIV [26]. In most sub-Saharan countries, including South Africa, mixed feeding is the norm and adherence to exclusive breastfeeding raises suspicions of HIV infection, and to avoid the stigma, women with and without HIV may elect to ‘mix feed’ [2628]. This is somewhat a contradiction given that, as discussed earlier, there is a perception that formula feeding is also associated with having HIV [22, 23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be a reflection of the misconception that only women with HIV need to practice exclusive breastfeeding, to prevent HIV transmission, and is optional for women without HIV [26]. In most sub-Saharan countries, including South Africa, mixed feeding is the norm and adherence to exclusive breastfeeding raises suspicions of HIV infection, and to avoid the stigma, women with and without HIV may elect to ‘mix feed’ [2628]. This is somewhat a contradiction given that, as discussed earlier, there is a perception that formula feeding is also associated with having HIV [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…It would have been more desirable to do a longitudinal study to compare intentions and actual postpartum practices in the same group of women, to determine how intentions translate to practice. The study design used was the most efficient use of available resources, and there are several challenges with mobility and loss to follow-up among postpartum women [28]. There could also have been a social desirability bias in reporting of infant feeding intentions and practices, and because the study was quantitative, we did not explore in detail the motivation behind the intentions and practices.…”
Section: Discussionmentioning
confidence: 99%
“…Some participants perceived breast milk as safe while others viewed it as a risk for transmitting HIV to the baby. This conflict of belief had already been documented in earlier studies conducted in Zambia [47]. This is generally linked to inadequate health education about the benefits of exclusive breastfeeding in the presence of HIV.…”
Section: Discussionmentioning
confidence: 88%
“…This could be as a result of the impact of interventions that have raised awareness on the importance of EBF and hence mothers practice it regardless of their HIV status. Hazemba et al, [62] in their exploratory qualitative study on the promotion of exclusive breastfeeding among HIV-infected mothers in Zambia, found that gaps in understanding benefits of exclusive breastfeeding and potential for behaviour change were a challenge. They attribute lower practice of EBF among HIV-infected mothers to lack of understanding of instructions provided by health workers.…”
Section: Discussionmentioning
confidence: 99%